Real Investment on Ground Water in Cauvery Basin Areas of Karnataka- An Economic Analysis - S., Raveesha; Chandrakanth, M. G.; Rudrapur, Shreeshail; Kusagur, Nagaraj; N., Ashoka (International Journal of Economic Plants, 2020)
In this study, irrigation wells located under canal command (GWCI) (Gadabanaalli), the irrigation wells located under tank command (GWTI) (Echanur), receiving the Hemavathy river water, with a water spread of 363 acres and another village Kibbanahalli where groundwater wells are located independently (called groundwater under sole irrigation GWSI), which depend only on rainfall source have been considered. Only farmers possessing irrigation wells in each of the three scenarios were chosen. A random sample of 35 farmers was drawn from each of the three scenarios, thus, totaling 105 for the purpose of this study. It was observed that the real investment was falling over the years with a range of Rs. 3137 to Rs. 6255 even though the nominal investment ranged between Rs. 19100 and Rs. 66600 for farmers in GWTI. Real investment on irrigation wells shows a declining trend in all the three situations. Thus, the real cost of groundwater is falling over time not exhibiting ricardian scarcity. In GCTI farmers, the real investment for working well was falling over the years with a range of Rs. 1815 to Rs. 6225 even though the nominal investment ranged between Rs. 20600 and Rs. 73987, the mean real investment per well was Rs. 5103, and the mean nominal investment per well was Rs. 40352. Considering the nominal cost of extraction of groundwater, it was clear that there was an increasing trend due to inflation and associated factors. However, the real cost of extraction was found to be consistent over the years.